Food contamination with fipronil alters gene expression associated with foraging in Africanized honey bees - Lima, Yan Souza [UNESP]; de Castro Lippi, Isabella Cristina [UNESP]; da Luz Scheffer, Jaine [UNESP]; Lunardi, Juliana Sartori [UNESP]; Alvarez, Marcus Vinícius Niz [UNESP]; Kadri, Samir Moura [UNESP]; de Oliveira Orsi, Ricardo [UNESP] (Springer Nature, 2024)
Taking into consideration that bees can be contaminated by pesticides through the ingestion of contaminated floral resources, we can utilize genetic techniques to assess effects that are scarcely observed in behavioral studies. This study aimed to investigate the genetic effects of ingesting lethal and sublethal doses of the insecticide fipronil in foraging honey bees during two periods of acute exposure. Bees were exposed to fipronil through contaminated honey syrup at two dosages (LD50 = 0.19 µg/bee; LD50/100 = 0.0019 µg/bee) and for two durations (1 and 4 h). Following exposure, we measured syrup consumption per bee, analyzed the transcriptome of bee brain tissue, and identified differentially expressed genes (DEGs), categorizing them functionally based on gene ontology (GO). The results revealed a significant genetic response in honey bees after exposure to fipronil, regardless of the dosage used. Fipronil affected various metabolic, transport, and cellular regulation pathways, as well as detoxification processes and xenobiotic substance detection. Additionally, the downregulation of several DEGs belonging to the olfactory-binding protein (OBP) family was observed, suggesting potential physiological alterations in bees that may lead to disoriented behaviors and reduced foraging efficiency.